Design and fabrication of solar light responsive new metal organic frameworks for photocatalysis / Nur Atiqah Surib - Nur Atiqah, Surib (2018)
Design and synthesis of multi-dimensional metal organic frameworks has attracted much attention not only due to their intriguing structures and unique properties, but also for their potential applications especially in catalysis. Recently, much effort has been devoted to develop new photocatalyst based on MOFs, motivated largely by a demand for solving pollution problems in view of their potential applications in the green degradation of organic pollutants. MOFs, known as coordination polymers are crystalline materials constructed from metal ions or clusters bridged by organic ligands to form one-, two-, or three-dimensional infinite networks. There are several methods have been applied for synthesis of MOFs particularly solvothermal, hydrothermal, microwave-assisted, electrochemical, mechanochemical and sonochemical synthesis. In this work, new Cadmium and Copper based Metal Organic Framework (MOF) was synthesized under hydrothermal and solvothermal conditions. Its structure was resolved by single crystal X-ray diffraction and further characterized by Powder X-ray diffraction (PXRD), Field Emission Scanning Electron Microscopy (FESEM), Infrared Spectra (IR), Thermogravimetric (TGA), UV-Vis, Photoluminescence (PL) and X-ray photoelectron spectroscopy (XPS) analysis. The Cd-MOF and Cu-MOF were photocatalytically active for degradation of 2-chlorophenol (2-CP) under solar light irradiation where 69% and 100% of phenol removal was observed respectively. To improve photocatalytic activity of Cd-MOF, different metal ions such as Ag+, Fe3+ and Zn2+ were introduced into the framework through ion-exchange reaction. The UV-Vis results revealed that Fe-Cd-MOF showed an enhanced photoresponse in the visible region, whereas the photoresponse of Ag-Cd-MOF and Zn-Cd-MOF in the ultraviolet light region. Photocatalytic performances of synthesized materials were investigated fordegradation of 2-CP. Among them, Cd-MOF intercalated with Fe3+ exhibited excellent photocatalytic activity compared with Cd-MOF, degrading 92% of 2-CP in 5 hours. It can be attributed to the intercalation of Fe3+, which reduced energy gap of pure MOF, thus increases photocatalytic efficiency.